Riding in cars with boys - Marshall, Penny; Ward, Morgan; Barrymore, Drew; Zahn, Steve, 1968-; Garcia, Adam; Zimmer, Hans; Pereira, Heitor; Donofrio, Beverly; Gracie Films; Columbia TriStar Home Video (Firm) (Culver City, CA : Columbia TriStar Home Video, 2002)
A dramatization of one young woman's journey from hoodlum to mother to successful writer.
Based on the book by Beverly Donofrio.
Features: Drew Barrymore commentary, four behind the scenes featurettes, HBO making of special, theatrical trailers, filmographies, animated menus, production notes, scene selections.
Director of photography, Miroslav Ondricek; production design, Bill Groom; editors, Richard Marks, Lawrence Jordan; music, Hans Zimmer, Heitor Pereira.
Drew Barrymore, Steve Zahn, Adam Garcia, Brittany Murphy, Lorraine Bracco, James Woods.
MPAA rating: PG-13.
DVD Dolby digital 5.1.
Keywords: Donofrio, Beverly -- Drama; Donofrio, Beverly -- Film and video adaptations; Teenage mothers -- Drama; Authors, American -- 20th century -- Drama; Video recordings for hard of hearing people; Based on the book; Feature films; Comedy films